(untitled) (R&D Journal, 2023)
This study focuses on experimentally validating the performance of XFOIL, a sophisticated software airfoil analysis tool used for approximating lift and drag coefficients. XFOIL output data was incorporated into a theoretical model simulating a variable pitch rotor system operating in a hovering state. The output of the Blade Element Momentum Theory (BEMT) rotor model is compared to thrust and power output performance data collected from a constructed rotor test bench and analysed in MATLAB. Using XFOIL as input, the BEMT rotor model was observed to yield good robust results when compared to experimental data, but demonstrated sensitivity to airfoil performance characteristics, laying the groundwork for future empirical validation. In comparing BEMT model performance, it was interesting to find that thrust performance remained within tolerance in contrast to an overprediction of rotor power output resulting from XFOIL drag at high blade pitch angles. Upon further interrogation by means of variable isolation, XFOIL demonstrated instability resulting from sensitivity to variability of model constraints. Modification of rotor geometry definitions or environmental constants beyond the test environment framework showed simulated systems may not necessarily behave reliably nor enhance output performance. This highlights the critical importance and utility of experimentation for understanding theoretical model behaviour or validating simulation output performance.